Preconception Counseling in Couples Undergoing Fertility Treatment - Nekuei, Nafisehsadat (Int J Fertil Steril, 2012)
BACKGROUND: The preconception period is crucial to fertility and pregnancy health. Offering education and counseling to couples being treated for infertility improves the outlook of treatment. The aim of this study is to assess preconception education and counseling in a population of Iranian couples treated for infertility. MATERIALS AND METHODS: This is a cross-sectional study of 268 individuals who presented to fertility clinics across the city of Isfahan, Iran. Questionnaires and patient records were used to collect data. We evaluated the components of standard preconception counseling (lifestyle, diet, sexual health, substance abuse, and social counseling) versus preconception counseling offered to couples that were receiving infertility treatment (failure, follow-up, and side effects of treatment). RESULTS: We found that no counseling had been given to about 76.9% about lifestyle, 70.9% about diet, 90.7% about sexual health, and 90.7% about the psychosocial aspects of infertility. No counseling had been given to 46.6% of individuals about a follow-up and also to 46.6% of individuals about the side effects of treatment. In more than 75% of the cases, counseling was offered to couples whose etiology of infertility was unknown. CONCLUSION: We have found serious flaws in the education and preconception counseling of infertile Iranian couples; action is required by medical and health teams to address these shortcomings.